Screening of upland-rice landraces for resistance to rice blast disease (Magnaporthe oryzae) - Agbowuro, Gbenga Oluwayomi; Ayeyo, Morolake Elizabeth; Awoyemi, Sola Olawale; Aigbokhan, Omoyeme Felicia (Journal of Pure and Applied Agriculture, 2023)
Rice blast disease (Magnaporthe oryzae) is one of the major biotic factors limiting rice production. An experiment was conducted in four locations to screen and identify upland rice accessions that are resistant to Magnaporthe oryzae. 25 upland rice landraces were collected and screened against Magnaporthe oryzae by artificial inoculum under the field condition in four locations for two cropping seasons. The experiments were laid in a Randomized Complete Block Design with three replications across the locations. Data were collected on grain yield, the weight of 1000 seeds, numbers of tiller per plant, panicle weight, grains per panicle, and plant height. Disease scoring was done using the Standard Evaluation System of the International Rice Research Institute and analyzed with IRRI STAR software. The screening result revealed that none of the 25 prominent upland rice landrace accessions is highly resistant or resistant. Five accessions; Acc. 1, Acc. 2, Acc. 7, Acc. 10, and Acc. 22 were moderately resistant, 11 accessions were moderately susceptible while eight accessions were susceptible. None of the accessions screened is highly susceptible to the pathogen. All moderately resistant accessions that gave high grain yield could be used as a gene pool for Magnaporthe oryzae resistance breeding for cultivar improvement except accession 22 that recorded a low grain yield. The use of the identified moderately resistant accessions with high yield by farmers is encouraged pending the time commercial Magnaporthe oryzae resistant cultivars will be readily available and accessible in rainforest and derived guinea savanna agro-ecological zones of Nigeria. © 2021 Department of Agricultural Sciences, AIOU